INUNDATION ANALYSIS OF SOUTH JAKARTA JALAN TIONG AREA USING HEC-RAS - Mohammad Imamuddin; Rizki Priya Ramadan (University Muhammadiyah Jakarta, 2023)
The Tiong Channel is located on Jalan Tiong Karet Kuningan, South Jakarta, geographically located between 6°13'06.5